Analisis Semiotika Charles Sanders Peirce Makna Simbolik Model Dan Warna Tanjak Melayu - Cutra Aslinda; Dyah Pithaloka; Happy Wulandari (JKOMDIS : Jurnal Ilmu Komunikasi Dan Media Sosial, 2026)
This research examines Malay symbolism within the Tanjak, focusing specifically on its structural models and color variations. The study employs Charles Sanders Peirce’s semiotic framework, utilizing his triadic model of meaning consisting of the sign, object, and interpretant. The primary objective is to decipher the symbolic significance of the Tanjak’s design elements through this semiotic lens. This study uses a qualitative approach of content analysis of Charles Sanders Peirce’s semiotic model. The results of the analysis show that Tanjak symbolizes the identity and the originality of the wearer. That by seeing someone using a certain Tanjak, we can identify his place of origin, his position in society, and his lineage he came from. Also, the intentions and purpose of his visit to an event. Therefore, the use of Tanjak by individuals who are given as symbols that will be imposed on guests who come from within the country and abroad should pay attention to the model, color and the person who uses the Tanjak. For them to be more wise, careful and respectful toward the cultural heritage so that it is accordance with its designation.The results of this research analysis consist of two parts, First: there are four tanjak models, Elang Menyongsong Angin with meaning wisdom and precision, Dendam Tak Sudah with meaning affectioan, Tebing Runtuh with meaning leadership  and Pial Ayam with meaning courage. Second; tanjak color variations, Tanjak Elang Menyongong Angin in black and silver, Tanjak Dendam Tak Sudah in yellow, Tabjak Tebing Runtuh in black and golden yellow, Tanjak Pial Ayam in green and golden yellow